2017
DOI: 10.1590/1678-4766e2017015
|View full text |Cite
|
Sign up to set email alerts
|

Influência da idade do hospedeiro e da aprendizagem no comportamento quimiotáxico e no parasitismo de Trichogramma pretiosum

Abstract: ABSTRACT. Infl uence of host age and learning on chemotactic behavior and parasitism of Trichogramma pretiosum. Trichogramma pretiosum Riley, 1879 reared on Ephestia kuehniella Zeller, 1879 eggs, have been used in biological control of Spodoptera frugiperda (J. E. Smith, 1797). However, host age and experience just after emergence might have some infl uence on parasitism and parasitoid behavior. This study evaluated the infl uence of S. frugiperda host age and egg odor experience, on chemotactic behavior and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…According to age of the host egg, change in its physical and chemical characteristics is the factor that has been more influential in the development of the parasitoid, as it was demonstrated in this study. The authors Vargas et al (2017) observed similar results. However, Polanczyk et al (2007) found that T. exiguum presented a better rate of parasitism when eggs of crucifer moths had 72 hours in embryonic development.…”
Section: Parasitismsupporting
confidence: 53%
See 1 more Smart Citation
“…According to age of the host egg, change in its physical and chemical characteristics is the factor that has been more influential in the development of the parasitoid, as it was demonstrated in this study. The authors Vargas et al (2017) observed similar results. However, Polanczyk et al (2007) found that T. exiguum presented a better rate of parasitism when eggs of crucifer moths had 72 hours in embryonic development.…”
Section: Parasitismsupporting
confidence: 53%
“…This correlation can be found in studies by Stinguel et al (2013) between 0.82 and 1, Zuim et al (2013) between 0.57 and 0.91, where sexual ratio in M. latipes eggs presented a ratio varying from 0.82 to 1 when the parasitoid was T. pretiosum, and 0.57 and 0.91 for T. exiguum. However, Vargas et al (2017) used T. pretiosum in S. frugiperda host and the rates varied from 0.46 to 0.50.…”
Section: Sexual Ratiomentioning
confidence: 99%
“…We conclude that the results of this work show that the reproductive state of males and females of A. calandrae (virgin or mated) does not affect the attractiveness to the volatile larvae or pupae with or without diet, but prior experience with the host alters the response of paired females. In applied context, the parasitoid learning could help to develop strategies for behavior manipulation and increase the impact of biological control (Meirelles et al 2009, Vargas et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Although parasitoids have an innate preference for certain odors, some species can optimize foraging through learning (Turlings et al, 1993; Vargas et al, 2017; Pires et al, 2021). Learning is a change in behavior that occurs as a consequence of individual experience and may induce memory formation, i.e., the ability to encode, store, and retrieve acquired information (Kandel, 2001; Dudai, 2002).…”
Section: Introductionmentioning
confidence: 99%